Immunologic and Radiographic Status in Newly Diagnosed Adults with Human Immunodeficiency Viral Infection at a General Outpatient Clinic of a Tertiary Hospital, North-west, Nigeria - Ramatu Abubakar; Tokan Silas Baduku; Amos Kadashi Isuwa; Karimah Saleh Abdulhamid (Nigerian Journal of Medicine)
Background: Human immunodeficiency virus (HIV) targets the body’s immune system and renders the body susceptible to varieties of opportunistic infections. Tuberculosis (TB) is one of the common opportunistic infections in person with HIV Infection. Aim: The study aimed to radiologically screen for pulmonary TB (PTB) and determine immunological status of persons newly diagnosed with HIV-infection attending HIV Counselling and Testing (HCT) unit at General Out-Patient Clinic (GOPC) of Barau Dikko Teaching Hospital (BDTH), Kaduna. Materials and Methods: This is a retrospective study from records of all cases diagnosed newly with HIV infection at HCT unit, GOPD, BDTH, Kaduna, from 1st January, 2023 to 31st December, 2023. A total of 120 folders were retrieved and analysed. Data on age, sex, blood pressure, immunological status, chest X-ray (CXR) and body mass index were analysed by means of descriptive statistics. Results: High proportions of the patients/clients (27.5%) were within the age of 31–40 years. Majority were female (62%). The cluster of differentiation 4 (CD4) counts of most of the patients/clients 55 (45.8%) was below 200 cells/mm3 and only 6 (5%) of the CXRs findings were suggestive of PTB. Conclusion: The immunologic status of most patients/clients was found to be very low at diagnosis and 5% of patients had CXR features suggestive of PTB. There should be regular screening of HIV infection at GOPC and routine CXR for newly diagnosed HIV-infected persons.